2012
DOI: 10.1158/0008-5472.sabcs12-p1-07-06
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P1-07-06: Effect of biospecimen variables on proteomic biomarker assessment in breast cancer

Abstract: Background: PI3K/Akt/mTOR signaling is being actively pursued as a therapeutic target. We sought to determine how tumor heterogeneity and biospecimen variables affect assessment of PI3K/Akt/mTOR pathway activation. Methods: Intraoperative image-guided core-needle biopsies (CNB) of primary breast tumors were prospectively collected in 53 patients with invasive breast cancer. After surgery, specimens were collected from the center and periphery of the excised tumor. CNB, central and peripheral sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The vast majority of cases (69% of pure DCIS and 75% of DCIS adjacent to IBC) harboring PTEN or INPP4B loss of expression, or PIK3CA or AKT1 mutations, displayed pAKT expression, whereas pS6 expression was found in 6% and 21% of pure DCIS and DCIS adjacent to IBC harboring these molecular aberrations. The lack of pAKT and pS6 expression in cases with alterations in these genes may stem from the fact that we have i) assessed pAKT and pS6 expression in surgical specimens and that previous analyses have shown that their immunohistochemical assessment is affected by pre-analytical variables, and its expression levels are significantly lower in surgical specimens than in core biopsies(48, 49); and ii) employed antibodies that recognize only a few phosphorylation sites of AKT (i.e. Ser473) and S6 (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vast majority of cases (69% of pure DCIS and 75% of DCIS adjacent to IBC) harboring PTEN or INPP4B loss of expression, or PIK3CA or AKT1 mutations, displayed pAKT expression, whereas pS6 expression was found in 6% and 21% of pure DCIS and DCIS adjacent to IBC harboring these molecular aberrations. The lack of pAKT and pS6 expression in cases with alterations in these genes may stem from the fact that we have i) assessed pAKT and pS6 expression in surgical specimens and that previous analyses have shown that their immunohistochemical assessment is affected by pre-analytical variables, and its expression levels are significantly lower in surgical specimens than in core biopsies(48, 49); and ii) employed antibodies that recognize only a few phosphorylation sites of AKT (i.e. Ser473) and S6 (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Third, given the evidence to suggest that low-and high-grade DCIS and IBCs are likely to evolve through distinct pathways (reviewed in(1)), we have focused only on the subset of high-grade lesions; hence, our conclusions should be considered relevant only to high-grade disease. Fourth, the surrogate markers employed to determine activation of the PI3K pathway, pAKT and pS6 immunohistochemistry, have been shown to be affected by pre-analytical parameters, including delayed fixation and the type of specimen(48, 49). Although the frequency of PI3K pathway activation may have been underestimated in this study due to the use of surgical specimens, given that all tissues were collected during the same time frame at a single institution, the reduction in pAKT and pS6 expression driven by pre-analytical parameters should be equally prevalent among all groups.…”
Section: Discussionmentioning
confidence: 99%